(untitled) (Intent Research Scientific Journal, 2023)
The article contains important statements from many scientific treatises about the factors that directly form the concept and many opinions about it. Also, in cognitive linguistics, information is given that concepts, categories, concepts, etc., are expressed through different linguistic units and have their own conceptual signs.